OUTSOURCING PEGAWAI DI LINGKUNGAN INSTANSI PEMERINTAH - Janry Haposan U.P Simanungkalit (Jurnal Manajemen Kepegawaian, 2009)
The objectives of this study are to map job or work area that applies outsourcing, particularly human resources(HR), describe form and reason implement HR outsourcing, analyze the role and risk of HR outsourcing,and formulating policy alternative as an effort to anticipate in implementing HR outsourcing at governmentinstitution. This study result shows that the HR outsourcing job or work area are Administration, Health,Technical, Education, Security, Cleanliness, Orderliness and other special work areas (Non-Core Competenceof government institution). The HR outsourcing form that is applied by government institution is with providerand non-provider. The main role of HR outsourcing is as an effort to handle HR needs on job or work area asnon-core competence of government institution. Policy implementation step in connection with implementingHR outsourcing at governmental institution in the future are to identify HR outsourcing needs, establish the lawand strategy in performing HR outsourcing, special management of HR outsourcing, maintaining commitmentand collaboration all stakeholder, monitoring and performing evaluation HR outsourcing periodically to be